Experimental and Computational Study on the Tensile and Flexural Properties of Polylactic Acid filled with Boron Nitride Nanoplatelets - Harishbabu Sundarasetty; Santosh Kumar Sahu (Fracture and Structural Integrity)
Our research described in this paper focused on fabricating and characterising polylactic acid (PLA) composites reinforced with randomly dispersed boron nitride nanoplatelets (BNNP). The integrated experimental analysis with the Finite Element Method (FEM) computational simulation employed a multiscale modelling approach used to evaluate the effects of BNNP fillers at varying weight fractions (i.e. 0.005% to 0.04%). The simulations utilised Representative Volume Elements (RVEs) with 1 x 1 x 1 μm dimensions, incorporating randomly dispersed BNNP to mimic the realistic composite behaviour. The modulus predicted through the RVE approach was validated against empirical studies and pre-existing micromechanical models to ensure accuracy and reliability. The empirical findings revealed significant enhancements in the modulus of elasticity, tensile strength and flexural strength of the PLA reinforced with BNNP composites exhibiting improvements of 17.43%, 40% and 61% respectively at elevated filler concentrations of 0.005, 0.01,0.02,0.03 and 0.04. The Scanning Electron Microscopy (SEM) analysis of the fracture surfaces indicated a transition from ductile to brittle fracture patterns as the BNNP content increased, underscoring the reinforcing effect of the nanoplatelets. Flexural testing further validated improvements in the material rigidity and resistance to bending. The Finite element analysis (FEA) simulations strongly correlated with the experimental data, with deviations remaining within an acceptable range. This integrated approach underscores the efficacy of BNNP fillers in enhancing the mechanical attributes of PLA, yielding significant perspectives for developing eco-friendly composite materials exhibiting superior performance features.